Defensoría del pueblo, supervisión penitenciaria y reformas durante el COVID-19 - Ytokazu Minami, Gustavo Raúl (2021)
The penitentiary system and its reforms have struggled with their formulation and implementation in order to fulfill its constitutional mandate of re-education, rehabilitation and reincorporation of former convicts into society. We present an analysis of the challenges that the State’s administrative capacity faces towards the Peruvian Penitentiary System in its complex adaptive system and the penitentiary supervision during the pandemic under charge of the Ombudsman. We conclude that an integral reform includes the Ombudsman as a National Torture Prevention Mechanism (NPM), and as a congregator for other State and Civil Society Actors for the implementation of long-term sustainable actions.